2017
DOI: 10.1371/journal.pgen.1006611
|View full text |Cite
|
Sign up to set email alerts
|

ELLI-1, a novel germline protein, modulates RNAi activity and P-granule accumulation in Caenorhabditis elegans

Abstract: Germ cells contain non-membrane bound cytoplasmic organelles that help maintain germline integrity. In C. elegans they are called P granules; without them, the germline undergoes partial masculinization and aberrant differentiation. One key P-granule component is the Argonaute CSR-1, a small-RNA binding protein that antagonizes accumulation of sperm-specific transcripts in developing oocytes and fine-tunes expression of proteins critical to early embryogenesis. Loss of CSR-1 complex components results in a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 67 publications
3
34
1
Order By: Relevance
“…A mutagenesis screen for effectors of P-granule assembly and distribution isolated multiple alleles of a gene encoding the Argonaute protein CSR-1 ( Andralojc et al, 2017 ). Whole genome sequencing revealed that one of these alleles, csr-1(sam18) , also contained a linked Gly to Asp mutation in pqn-75 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A mutagenesis screen for effectors of P-granule assembly and distribution isolated multiple alleles of a gene encoding the Argonaute protein CSR-1 ( Andralojc et al, 2017 ). Whole genome sequencing revealed that one of these alleles, csr-1(sam18) , also contained a linked Gly to Asp mutation in pqn-75 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the inappropriate zygotic germline expression seen in starved daf-18 mutant PGCs was specific to VBH-1, we investigated another germline gene reporter: GLH-1::GFP (Germ Line Helicase), a component of germline-specific P granules (Gruidl et al 1996). We used an available GLH-1::GFP CRISPR allele (Andralojc et al 2017), and crossed it in from the male to examine zygotic protein expression. Like GFP::VBH-1, we found that in PGCs of starved daf-18 mutant animals, the level of zygotic GLH-1::GFP expression was significantly elevated compared to the wild type within a few hours of hatching ( Figure 4C).…”
Section: Levels Of Zygotic Vbh-1 and Glh-1 Are Inappropriately Elevatmentioning
confidence: 99%
“…All scale bars are 20 microns. For immunostained images ( Figure 4A/B/C), worms and embryos were fixed and stained with anti-GFP monoclonal and anti-PGL-1 polyclonal antibodies as previously described (Andralojc et al, 2017).…”
Section: Imaging P-granule Counts and Expression Intensitymentioning
confidence: 99%